Taking the Path Into the Dark Woods – Initial Industry Impact of the COVID-19 Pandemic - Thornberg, Adam (Frontiers in Cellular and Infection Microbiology, 2022)
During the initial onset of the COVID-19 pandemic, each industry experienced hardships. One area that has not been explored in great detail was how the diagnostic industry managed while bringing SARS-CoV-2 tests to the market. This perspective piece provides a sample view of what went on behind the walls of a diagnostic manufacturer that released one of the initial SARS-CoV-2 testing options, some of the barriers that were encountered, and how they could be overcome.